Residential preferences in residential location choice : household preferences in Penang Island, Malaysia / Hamizah Abdul Fattah, Nurwati Badarulzaman and Kausar Ali - Hamizah, Abdul Fattah; Nurwati, Badarulzaman; Kausar, Ali (Universiti Teknologi MARA, Perak, 2018)
Residential mobility attempts to address problems on households' life adjustments or the mismatch between residents' present needs and housing consumption. The desired preferences of each household may be complex to determine, but the trends or preferences in a residential area can be captured. Residential location choice stimulates residential mobility decision on the selection of a particular area. This study aims to identify residential preferences on relocation using a selected sample of 323 households in Penang who intend to move in the near future. Results show that residents prefer to move to other states than Penang. Therefore, determining residential preferences is necessary to develop corresponding housing policies.